La thermoluminescence comme prisme de l’étude du faux : application aux terres cuites chinoises - Armel Bouvier (Les Cahiers de Framespa, 2019)
The authentication of Chinese porcelain is quite complex. This is due to its intrinsic heterogeneity. Physical and chemical analyses of it components, which are now used in the authentication process, are part of a relatively young field of expertise : archaeometry. It is of the utmost importance to clearly understand what their contribution to authentication is and what are their limits. If thermoluminescence is the most suitable tool to provide chronological information on ceramics, its use is necessary but not sufficient to prove the consistency of an object with its presumed attribution. Several techniques can be used to enhance the authentication study. But it is crucial to determine the order of the different techniques and what kind of information they can provide. Analytical results are often the same but still enable the detection of forgeries, even the most intelligent ones. The application of analysis techniques on works of art for more than 10 years in the CIRAM laboratory is useful to illustrate forgers’ crafting, along with the art market variations.